The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9ra07057e
|View full text |Cite|
|
Sign up to set email alerts
|

Modelling and prediction of the thermophysical properties of aqueous mixtures of choline geranate and geranic acid (CAGE) using SAFT-γ Mie

Abstract: The properties of aqueous solutions of the CAGE deep eutectic solvent are predicted with the SAFT-γ Mie approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…In future work, we plan to incorporate this approach in the SAFT-g Mie group-contribution equation of state to develop models of complex organic ions as heteronuclear chains containing charged and uncharged segments, extending our recent work in this area. 163…”
Section: Discussionmentioning
confidence: 99%
“…In future work, we plan to incorporate this approach in the SAFT-g Mie group-contribution equation of state to develop models of complex organic ions as heteronuclear chains containing charged and uncharged segments, extending our recent work in this area. 163…”
Section: Discussionmentioning
confidence: 99%
“…Finally, aqueous solutions of carbon dioxide can be modelled accurately by assuming that water associates mainly with the CO 2 moiety of the bicarbonate anion, confirming quantum mechanical studies from the literature. In future work, we plan to incorporate this approach in the SAFT-γ Mie group contribution equation of state to develop models of complex organic ions as heteronuclear chains containing charged and uncharged segments, extending our recent work in this area 163 .…”
Section: Discussionmentioning
confidence: 99%
“…Hutacharoen et al , 27 Di Lecce et al. , 28 Febra et al , 29 and Haslam et al ( 30 ) have recently shown that, thanks to the rigorous thermodynamic concepts that the SAFT-γ Mie EoS, the thermodynamic platform can provide high-quality predictions of the solubility of pharmaceutical compounds in a range of solvents, as well as liquid–liquid and vapor–liquid equilibria, all key properties for industrial applications.…”
Section: Methodsmentioning
confidence: 99%